2007
DOI: 10.1007/bf03340244
|View full text |Cite
|
Sign up to set email alerts
|

Erfolgsfaktoren serviceorientierter Architekturen

Abstract: Erfolgsfaktoren serviceorientierter ArchitekturenServiceorientierte Architekturen (SOA) finden aufgrund des hohen Potenzials momentan große Beachtung. Demgegenüber steht ein geringer Wissens-und Erfahrungsstand innerhalb der meisten Unternehmen. Durch die Betrachtung von Erfolgsfaktoren für SOA werden Entscheidungsträgern die entscheidenden Hebel für eine erfolgreiche Einführung aufgezeigt. Dazu wurde sowohl eine qualitative State-of-the-Art-Analyse und Expertenbefragung als auch eine quantitative Erhebung mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Beside the small sample size and a high proportion of Germany-based IaaS providers, the study underlies the general weakness that the answers of the participants reflect their personal experience and opinion. Even if this corresponds with the common approach in the scientific community (e.g., [21,25]) and so-called perceived SDBMCs (particularly by senior managers) are widely consistent with the factual ones (e.g., [28,29]), possible distortions cannot be ruled out. Apart from that, Likert scales are prone to the central tendency biasthe tendency to place items in the middle of the scale [30].…”
Section: Limitationsmentioning
confidence: 88%
See 1 more Smart Citation
“…Beside the small sample size and a high proportion of Germany-based IaaS providers, the study underlies the general weakness that the answers of the participants reflect their personal experience and opinion. Even if this corresponds with the common approach in the scientific community (e.g., [21,25]) and so-called perceived SDBMCs (particularly by senior managers) are widely consistent with the factual ones (e.g., [28,29]), possible distortions cannot be ruled out. Apart from that, Likert scales are prone to the central tendency biasthe tendency to place items in the middle of the scale [30].…”
Section: Limitationsmentioning
confidence: 88%
“…The survey was launched in German and English using SoSciSurvey, a free survey tool for academic purposes. A pre-test with practitioners was omitted because the questionnaire was adjusted to already well-established question structures and scales (cf., [21,22,25]). Nevertheless, two scholars checked the survey for its intelligibility and consistency, which resulted in slight refinements.…”
Section: Survey Designmentioning
confidence: 99%
“…As Becker et al [7] have found in a literature review, the description of SOA value is often formulated in a very positive manner and lacks a critical perspective on the downsides of SOA. Therefore, a "critical perspective" on the SOA evaluation is the last criterion for a framework Afterwards, 29 business benefits of SOA were collected from various scientific and practical papers and books, including an expert study on SOA value potentials [7] The reasons for this broad selection are the alignment of theory and practice and the need for a holistic approach [8]. The business benefits have been analyzed and categorized in a 2-dimensional matrix, as described in section 4.…”
Section: Methodsmentioning
confidence: 99%
“…Only recently, a discussion of methodical requirements for evaluating SOA has begun. Examples include contributions focusing on success factors (Durst and Daum 2007), performance indicators (Fiedler and Seufert 2007) and profitability calculations (vom Brocke 2007a).…”
Section: Related Workmentioning
confidence: 99%